Development of an Optical Sensor Using a Molecularly Imprinted Polymer as a Selective Extracting Agent for the Direct Quantification of Tartrazine in Real Water Samples - Ruiz-Córdova, Gerson A. (2024)
This study presents a new optical sensor for tartrazine (TAR) quantification developed using a molecularly imprinted polymer (MIP) as the recognition element, with optical fiber serving as the supporting substrate. The fiber surface was functionalized with 3-(trimethoxysilyl)propyl methacrylate (MPS), and the fiber was coated with MIP using the precipitation polymerization method. The analysis of MIP immobilization on the functionalized optical fiber (FF) was conducted through the use of scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) techniques. Experimental parameters, such as contact time and fiber length, were adjusted in order to obtain the highest sensitive response signal for the functionalized optical fiber (FF-MIP). The fiber sensor, FF-MIP, exhibited a relatively higher response signal for tartrazine compared to other interfering dyes. The rapid and total desorption of the analyte from FF-MIP allowed the immediate reemployment of FF-MIP, which also presented an acceptable repeatability for the reflectance signal. The imprinting factors for the studied dyes were between 0.112 and 0.936 in front of TAR, 1.405, and selectivity factors were between 1.501 and 12.545, confirming the sensor selectivity. The FF-MIP sensor was successfully applied for tartrazine quantification in real water samples, where it yielded satisfactory results comparable to those of the HPLC reference method.